2017
DOI: 10.1016/j.neuro.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Decreased anxiety in juvenile rats following exposure to low levels of chlorpyrifos during development

Abstract: Exposure to chlorpyrifos (CPF) during the late preweanling period in rats inhibits the endocannabinoid metabolizing enzymes fatty acid hydrolase (FAAH) and monoacylglycerol lipase (MAGL), resulting in accumulation of their respective substrates anandamide (AEA) and 2-arachidonylglycerol (2-AG). This occurs at 1.0 mg/kg, but at a lower dosage (0.5 mg/kg) only FAAH and AEA are affected with no measurable inhibition of either cholinesterase (ChE) or MAGL. The endocannabinoid system plays a vital role in nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 72 publications
(102 reference statements)
4
40
0
Order By: Relevance
“…Importantly, there are sex-selective effects of decreased responsiveness to the muscarinic antagonist scopolamine on radial-arm maze reference memory performance in females (Levin and others 2001). Increased aggressive behavior was seen in CPF-exposed males, increased maternal responsiveness toward pups in CPF-exposed virgin females and reduced anxiety levels and motivation to build the nest and defend it from a male intruder in lactating females (Carr and others 2015; Ricceri and others 2003; Ricceri and others 2006; Venerosi and others 2008). Even though there are significant effects of exposure at late-postnatal stages, the comparison between distinct periods of brain development indicates that several of them tend to reduce in magnitude and fade during the course of postnatal development, which is consistent with evidence of higher susceptibility to OPs in younger animals.…”
Section: Organophosphates (Ops)mentioning
confidence: 99%
“…Importantly, there are sex-selective effects of decreased responsiveness to the muscarinic antagonist scopolamine on radial-arm maze reference memory performance in females (Levin and others 2001). Increased aggressive behavior was seen in CPF-exposed males, increased maternal responsiveness toward pups in CPF-exposed virgin females and reduced anxiety levels and motivation to build the nest and defend it from a male intruder in lactating females (Carr and others 2015; Ricceri and others 2003; Ricceri and others 2006; Venerosi and others 2008). Even though there are significant effects of exposure at late-postnatal stages, the comparison between distinct periods of brain development indicates that several of them tend to reduce in magnitude and fade during the course of postnatal development, which is consistent with evidence of higher susceptibility to OPs in younger animals.…”
Section: Organophosphates (Ops)mentioning
confidence: 99%
“…6). Postnatal CPF treatment at 0.5 mg kg −1 day −1 decreased anxiety in juvenile rats and yielded effects on the endocannabinoid system at a dose lower than that inhibitory for brain AChE (Carr et al, ).…”
Section: Neurodevelopmental and Neurobehavioral Effects Of Cpf In Rodmentioning
confidence: 99%
“…Two of three studies that measured brain AChE inhibition reported that gavage CPF administration from PND 10–16 (Carr et al, ) or CPF sc injection from PND 11–14 (Ricceri et al, ) showed significant brain AChE inhibition only at doses higher than those eliciting significant anxiety effects. Treatment of rat pups with CPF sc injections at 1.0 mg kg −1 day −1 from PND 1–4, which showed anxiety effects, also showed brain AChE inhibition; however, this was the lowest dose tested.…”
Section: Neurodevelopmental and Neurobehavioral Effects Of Cpf In Rodmentioning
confidence: 99%
See 2 more Smart Citations